ANALISIS PENGGUNAAN MODEL PROBLEM BASED LEARNING BERBASIS SMARTPHONE PADA PEMBELAJARAN SOSIOLOGI KELAS X SMA ISLAMIYAH - Jagky Gunawan; Yohanes Bahari; Izhar Salim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research is entitled “An Analysis of the Use of Problem-Based Learning Approach based on Smartphone in Sociology Learning of Tenth Grade in SMA Islamiyah”. The research method employed was descriptive in qualitative form. The data sources of this research were a sociology teacher and four students of Class X IPS 1 SMA Islamiyah Pontianak. The data collection techniques were interview, observation and documentation, while the data collection tools were an interview guideline, an observation and a documentation. The analysis of this research was presented in descriptive qualitative form with five informants, a sociology teacher and four students. The results showed that the sociology teacher had done planning, implementation and leaning outcomes assessment in implementing problem-based learning approach based on smartphone in sociology learning at Class X IPS 1 in SMA Islamiyah Pontianak. However, there were some imperfections in the implementation of problem-based learning approach. The sociology teacher did not perform the steps in problem-based learning approach that is, analysing and evaluating the problem solving process, for instance. In the learning outcomes assessment of problem-based learning approach based on smartphone, the sociology teacher did not assess the learning outcomes in the affective aspect (attitude). Keywords: Problem-Based Learning, The Use of Smartphone, Sociology Learning